Impact of crossbreeding and upgrading of nondescript cattle and buffaloes on livestock quality and income - HEGDE, NARAYAN G (The Indian Journal of Animal Sciences, 2023)
Upgradation of the progeny of low productive nondescript cattle through crossbreeding during 60’s, marked the involvement of marginal and small farmers who represented 85% of the land holders in India, in dairy industry. Various development organisations took initiatives to conserve local breeds of cows and buffaloes. To study the response of farmers to genetic improvement of cattle through crossbreeding and upgradation with native breeds, a field survey was conducted in 8 states where BAIF has been providing livestock breeding services. The study revealed that with reliable services, the population of crossbred cattle increased with significant reduction in nondescript cattle. Recently, due to aggressive propaganda on native cows, farmers have been gradually shifting to native breeds of cattle. Most of the farmers had no idea about the economics of native cows while the average milk yield of crossbreds was 100% to 150% higher. With regard to buffaloes, Murrah breed was popular. The programme enabled farmers to generate higher income by selling surplus milk and animals. Farmers covered under milk collection realized higher price. There was 200% to 400% increase in income of dairy farmers, based on the duration of their participation, number of cows owned, availability of feed and veterinary services, realization of price for milk, etc. The programme helped significant number of poor families to come out of poverty. However, as there is a move to shift from crossbreeding to upgrade with native breeds, it is recommended to study the economics of milch animals with other advantages and disadvantages to enlighten the farmers.